PERAN CUSTOMER ENGAGEMENT MEMEDIASI PENGARUH ATRIBUT PLATFORM DIGITAL DAN GAYA HIDUP DIGITAL TERHADAP REPURCHASE INTENTION - Anak Agung Gede Cahaya Trisna; Georgius Anders Mahadana Sridana; Made Arya Wijaya; Putu Bayu Surya Dharma Putra; Putu Yudi Setiawan; Ni Nyoman Kerti Yasa (BORJUIS: JURNAL OF ECONOMY, 2026)
The rapid development of digital technology has fundamentally transformed consumer behaviour patterns in Indonesia, particularly in the use of super-app platforms. This study aims to develop a conceptual model of the relationship between the variables of digital platform attributes, lifestyle and repurchase intention, with customer engagement acting as a mediating variable. This conceptual study employs the Stimulus-Organism-Response (S-O-R) paradigm as its theoretical framework, positioning digital platform attributes and lifestyle as the stimulus (S), customer engagement as the organism (O), and repurchase intention as the response (R). The conceptual model developed is complemented by propositions covering both direct and indirect pathways via mediation. Based on a review of previous research, digital platform attributes—including ease of use, speed of access, transaction security, quality of information, and service integration—are projected to have a positive influence on customer engagement. Similarly, alignment with a digital lifestyle is projected to enhance customer engagement and ultimately drive repurchase intention. Customer engagement is positioned as a key mediating mechanism that bridges external stimuli with repurchase behaviour. This study contributes to the development of an integrated conceptual model whilst providing a foundation for future quantitative research.